Safe and Healthy Food Preservation: Efficacy of Guava Leaves and Lemon Juice Extract on Fruits and Vegetables - Md. Esrafil; Ayasha Ahmed; Mausufa Akter; Toufika Arafin; Md. Sohag Ali; Md. Sajib Al Reza; Pratima Roy Dina; Syeda Huraiya Hasan Nishi (Knowledge Dynamics, 2024)
Background: Fruits and vegetables are naturally perishable and have a relatively limited shelf life. This study was designed to prolong the shelf life and remain nutritional value of various fruits and vegetables by using guava leaves extract and lemon juice extract (natural preservatives). Methods: Fruits and vegetables samples (amla, banana, grapes, bean, eggplant and tomato) were treated with three types of natural preservatives: guava leaves and lemon juice extract (GLE) 0.5% (boiled), lemon extract (LE) 15%, GLE 40% + LE 15%. Results: The study revealed that the moisture content varied from 18.03% to 95.41%. During the 10 days of experiment, samples treated with 0.5% GLE (boiled) preservatives exhibited better result than other two types of preservatives regarding the moisture content. Titratable acidity content varied from 0.05% to 2.25%. The pH value varied in the range of 2.47-6.01. The percentage of weight loss value ranged from 3.67 to 85.71. During the experiment period, weight loss was minimum almost in all samples treated with GLE 40%+LE 15% preservative. The vitamin C content in fruits and vegetables ranged from 1.60 mg/100mL to 68.46mg/100mL. The highest viable count was found in banana (46×104 CFU/ml) and the lowest was in Bean (9×104 CFU/ml). Conclusion: Among three types of preservatives, samples treated with 0.5% GLE (boiled) showed better result and minimum microbial growth.